Studies on character association and path coefficient for quantitative traits to yield and its attributes in garlic: Character association for quantitative traits to yield in garlic - Singh, R K; Rai, Mritunjay; Kumar, Mukul; Dwivedi, S V (Journal of Spices and Aromatic Crops, 2022)
Association between characters and path analysis in seventeen genotypes/lines of garlic (Allium sativum L.) was studied at the Vegetable Research Farm, BUAT, Banda during 2019 and 2020. The pooled data of correlation studies, revealed that gross yield plot-1 had positive and significant correlation with equatorial bulb diameter, weight of 20 bulbs and weight of 50 cloves at genotypic and phenotypic level respectively. This showed that improving these features could improve the crop’s physiological capacity to mobilise and translocate photosynthates to economically valuable organs (the bulb), perhaps increasing bulb yield as seen in the study. Yield was significantly and negatively correlated with bulb shape index, number of cloves bulb-1, and thrips plant-1 at genotypic level. The genotypic path coefficient analysis showed that equatorial bulb diameter and plant height had the highest positive direct effect on bulb yield. Weight of 20 bulbs and collar thickness had negative direct effect on bulb yield. Positive direct effect of equatorial bulb diameter and plant height indicated good scope for improvement in bulb yield by selecting genotypes having bigger bulb along with increased plant height.